Analisis Pengaruh Perkembangan Sektor Keuangan Terhadap Industrialisasi pada Negara Industri Baru di Asia Pasifik - Shaghi Ratu Sa’bani; Yollit Permata Sari (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2021)
This study examines the influences of financial development on the industrialization by combining cross section data for the five newly industrialized countries in Asia Pacific with time series data from the period 2000 to 2019. The results by using fixed effect model showed that: (1) financial depth has a negative and significant on the industrialization in newly industrialized countries in Asia Pacific; (2) financial efficiency has a positif and significant on the industrialization in newly industrialized countries in Asia Pacific; (4) financial stability has a negative and significant on the industrialization in newly industrialized countries in Asia Pacific; and (5) financial depth, financial efficiency and trade openness and foreign direct investment inflow have significantly affected the industrialization in newly industrialized countries in Asia Pacific.